Is Modified K-line a Powerful Tool of Surgical Decision Making for Patients With Cervical Spondylotic Myelopathy?. Issue 9 (November 2019) - Hirai, Takashi; Yoshii, Toshitaka; Inose, Hiroyuki; Yuasa, Masato; Yamada, Tsuyoshi; Ushio, Shuta; Onuma, Hiroaki; Hirai, Keigo; Kobayashi, Yutaka; Utagawa, Kurando; Hashimoto, Jun; Kawabata, Atsuyuki; et al.
Abstract : Study Design: Prospective observational single-center study. Objective: To evaluate anterior decompression and fusion (ADF) or posterior surgery (PS) for patients with cervical spondylotic myelopathy (CSM) using the modified K-line (mK-line) and to compare clinical and radiologic outcomes between these 2 techniques. Summary of Background Data: The authors have previously reported that insufficient posterior decompression is often seen after laminoplasty for CSM in patients with preoperative anterior clearance of the spinal cord <4 mm on the basis of the mK-line. However, to our knowledge, no study has investigated the role, if any, of the mK-line in surgical decision making for patients with CSM. Methods: A total of 87 patients were enrolled who underwent surgery for treatment of CSM between 2011 and 2015 at our hospital and who could be followed up for at least 2 years. ADF was selected as a more favorable procedure than PS in patients with anterior spinal clearance of <4 mm on preoperative midsagittal magnetic resonance imaging. On the basis of the Japanese Orthopedic Association (JOA) scoring system for cervical myelopathy, the rate of recovery of the JOA scores at 2 years after surgery was investigated as a clinical outcome to compare these 2 groups. Results: Mean age was 65.1 (±12.9) years in the ADF group (n=26) and 70.5 (±8.6) years in the PS group (n=61). In the PS group, 10 patients underwent posterior decompression with fusion. Mean preoperative and postoperative JOA scores were 10.5 and 14.1 points in the ADF group and 9.8 and 13.1 points in the PS group, respectively, showing no significant difference in recovery rate of JOA score between the ADF (58.9%) and PS (47.1%) groups. However, patients with a minimum interval between the mK-line and the anterior compression factor on the midsagittal image (minimum interval of the spinal cord) <4 mm tended to have unsatisfactory outcomes (recovery rate 29.6%) compared with patients with minimum interval of the spinal cord >4 mm (53.6%, P =0.07) in the PS group. Conclusion: Preoperative intervention using the mK-line is useful to predict residual cord compression and might homogenize postoperative clinical outcomes in both anterior surgery and PS.